Mpox and monkeypox virus: special considerations for athletes in contact sports - Smoliga, J. M. (Sports Medicine, 2023)
Monkeypox virus infections (mpox) in humans have become increasingly common since the virus was first identified in 1970. Coverage of the ongoing mpox outbreak has emphasized the role of skin-to-skin contact in monkeypox virus transmission and has focused on the community of men who have sex with men. While close contact from sexual activity is currently the main mechanism of monkeypox virus transmission, the potential for contact sports to exacerbate the 2022 outbreak has largely been overlooked. Infectious diseases rapidly spread in sports with significant skin-to-skin contact (i.e., wrestling and other combat sports, American football, and rugby). Mpox has not yet reached the athletic community, but once it does, it may follow a similar pattern of other infectious skin diseases in sports. Thus, it is critical to initiate a discussion of the risk of mpox and potential preventive measures within a sports context. This Current Opinion aims to provide stakeholders within the sports community with a brief review of infectious skin diseases in athletes, an overview of mpox and why it is relevant to athletes, and recommendations to reduce the risk of monkeypox virus transmission within sports settings. Guidelines for sports participation in athletes exposed to mpox and those with suspected, probable, and confirmed cases of monkeypox are provided.